2004
DOI: 10.1038/sj.bjc.6602127
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed balance of expression between XIAP and Smac/DIABLO during tumour progression in renal cell carcinomas

Abstract: Dysregulation of apoptosis plays an important role in tumour progression and resistance to chemotherapy. The X-linked inhibitor of apoptosis (XIAP) is considered to be the most potent caspase inhibitor of all known inhibitor of apoptosis-family members. Only recently, an antagonist of XIAP has been identified, termed Smac/DIABLO. To explore the relevance of antiapoptotic XIAP and proapoptotic Smac/DIABLO for tumour progression in renal cell carcinomas (RCCs), we analysed XIAP and Smac/DIABLO mRNA and protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
56
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 47 publications
7
56
0
Order By: Relevance
“…The present immunohistochemical data are consistent with previous reports that XIAP expression was increased in RCC compared with normal kidney and XIAP levels Yan et al, 2004;Mizutani et al, 2007) correlated with tumour progression. Despite several previous attempts, there is still no consensus on the significance of Smac to the malignant potential of RCC (Yan et al, 2004;Mizutani et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The present immunohistochemical data are consistent with previous reports that XIAP expression was increased in RCC compared with normal kidney and XIAP levels Yan et al, 2004;Mizutani et al, 2007) correlated with tumour progression. Despite several previous attempts, there is still no consensus on the significance of Smac to the malignant potential of RCC (Yan et al, 2004;Mizutani et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…Despite several previous attempts, there is still no consensus on the significance of Smac to the malignant potential of RCC (Yan et al, 2004;Mizutani et al, 2005). Here, we found that Smac levels were lower in RCC than in normal kidney; however, the levels were similar in various tumour tissues.…”
Section: Discussionmentioning
confidence: 33%
See 1 more Smart Citation
“…Thus, it can antagonise both the mitochondrial regulated (intrinsic) and death-receptormediated (extrinsic) apoptotic pathways (Hengartner, 2000). In clinical investigations, the protein has been shown to be overexpressed in a number of different tumours relative to normal tissue (Hofmann et al, 2002;Krajewska et al, 2003;Shiraki et al, 2003) and high expression is often associated with poor patient outcome (Tamm et al, 2000(Tamm et al, , 2004Ramp et al, 2004;Yan et al, 2004) and resistance to chemotherapy (Parton et al, 2002).…”
mentioning
confidence: 99%
“…In this context, the functional loss of the tumor-suppressor p53 (Brown and Attardi, 2005), the upregulation of antiapoptotic molecules, for example, bcl-2, c-FLIP, XIAP (Medema et al, 1999;Kim et al, 2004;Yan et al, 2004), or the downregulation of proapoptotic proteins, for example Smac/Diabolo and Bid (Erler et al, 2004;Yan et al, 2004), have been extensively reported. Another important determinant of antiapoptotic protection in cancer cells, including PDAC, is the constitutive activation of the transcription factor NF-kB (Wang et al, 1999;Schmid and Adler, 2000).…”
Section: Introductionmentioning
confidence: 99%